Opini Publik dan Persepsi Pemilih Terhadap Pencalonan Pasangan Airin Rachmi Diany Dan Ade Sumardi Pada Pilgub Banten Tahun 2024 - Nuryani, Najli Aidha (STISIPOL Raja Haji, 2026)
The 2024 Banten gubernatorial election has become a significant focal point due to the candidacy of Airin Rachmi Diany and Ade Sumardi, particularly in the context of dynastic politics that have long shaped the region’s political dynamics. This research aims to analyze public opinion and voter perceptions of this pair of candidates. Using descriptive qualitative methods and in-depth interviews, primary data was obtained from voters in Banten, supported by secondary document analysis such as media coverage and survey results.The results showed that voters' perceptions were fragmented. A correlation has been demonstrated between educational background and stance on dynastic politics, with highly educated individuals exhibiting a tendency towards critical evaluation of such phenomena. Conversely, individuals with limited formal education demonstrate a greater inclination to prioritize tangible outcomes. The support for Airin-Ade is predominantly influenced by their documented achievements; however, the prevailing social stigma associated with political dynasties poses a substantial challenge, particularly among the younger demographic, which exhibits a pronounced aversion to the prevailing influence of family politics. The mass media has been identified as a pivotal factor in shaping public opinion, exerting its influence through both positive and negative forms of coverage. In conclusion, while the concept of political dynasty carries a stigma, the Airin-Ade pair can garner support by underscoring individual capabilities, articulating a concrete vision and mission, and employing digital-based communication strategies to engage young and critical voters.